MAULID NABI CELEBRATION ARENA IN THE CONTEXT OF SOCIAL SCIENCE - Teguh Hidayatul Rachmad; Gerson Ralph Manuel Kho (International Conference on Social and Islamic Studies, 2021)
The celebration to commemorate Prophet Muhammad’s Birthday knows as MaulidNabi, which held at Bangkalan, Madura, exhibit a capital clash within Madurese’s societalculture. Maulid Nabi celebration or in local language called Muludhen, demonstrate fourcapitals explained by Bourdieu which possessed by Madurese peoples. This studyemployed descriptive qualitative method, with every person from each social class as akey informant. Muludhen celebration displayed a rare spectacle of Madurese’s genuinecultural identity, which are eroded by bourgeoism and in local language “tertekandhibik”. The festivities of the Muludhen celebration, goes hand in hand with theeconomical level in the Madurese Society. The contention of the Bourdieu’s fourcapitals, held to exhibit their societal status within the Madurese Society. Nevertheless,Muludhen which are held at the Mosque or at the private property like local people’shouse, held one major intention; to preserve harmony and fraternity within MadureseSociety.